PERANCANGAN ULANG UI/UX DESIGN APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) - Tendy Ilhamudin Firdaus; Meriska Defriani; Candra Dewi Lestari (POLITEKNIK PIKSI GANESHA, 2023)
Digital ID or Digital Population Identity is an important innovation by the Directorate General of Civil Registration of the Ministry of Home Affairs in Indonesia to digitize population documents and provide easy access to Indonesian citizens through their mobile phones. Although the Digital Population Identity application has gained significant popularity with a rating of 3.4 on the Play Store and thousands of user reviews, observations from user feedback have revealed several challenges that hinder users from utilizing the application according to their needs. The initial evaluation using the System Usability Scale (SUS) method indicates the need for improvements in the interface of the Digital Population Identity application, despite receiving a